TATABBU IN THE WORK OF AMIRI (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article aims to investigate the significance of Tatabbu, a recurring theme in the literary works of Amiri. Through an in-depth analysis of Amiri's writings, this study examines the various aspects of Tatabbu, including its contextual interpretation, symbolic representation, and narrative function. The article utilizes an annotated approach to provide a comprehensive understanding of Tatabbu, accompanied by keywords, input section, methods section, results section, discussion section, and conclusions with suggestions for further research.